Fabrication of Oriented Colloidal Crystals from Capillary Assembly of Polymer‐Tethered Gold Nanoparticles. Issue 13 (10th February 2022) - Gao, Yutong; Zhou, Youshuang; Xu, Xiangyun; Chen, Chungui; Xiong, Bijin; Zhu, Jintao
Abstract: Self‐assembled colloidal crystals (CCs) or nanoparticle (NPs) superlattices have attracted significant attention due to their potential applications in many fields. However, due to the complex interactions that govern the self‐assembly, it is difficult to predict and control the superstructure organization of CCs. Herein, a facile yet effective way is demonstrated to fabricate oriented CCs from capillary assembly of polymer‐tethered gold NPs (AuNPs). Assembly mechanism of polymer‐tethered AuNPs and their superlattice structures are systematically studied by in situ small‐angle X‐ray scattering (SAXS) technology. The results show that the oriented CCs of polymer‐tethered AuNPs can be obtained upon solvent evaporation in a capillary tube and the oriented structure is mainly determined by the chain length of polymer ligands and size of AuNPs. Assembly of AuNPs tethered by short‐chain ligand can result in oriented face‐centered cubic (fcc) superlattice, whereas AuNPs tethered by long‐chain ligand can assemble into an oriented body‐centered tetragonal (bct) superlattice structure. Interestingly, in situ SAXS study shows that for the sample of bct superlattice structure, a transformation from fcc to bct superlattice upon solvent evaporation is observed, which strongly depends on chain length of ligands. This work provides a useful guide for polymer‐tethered AuNPs to prepare orientation colloidal crystals. Abstract : A facile yet effective route is demonstrated to fabricate oriented colloidal crystals with face‐centered cubic (fcc) and body‐centered tetragonal (bct) superlattices via capillary assembly of polymer‐tethered gold nanoparticles (NPs). During solvent evaporation, transformation from fcc to bct superlattice is observed in an in situ small‐angle X‐ray scattering study, strongly depending on the ratio of polymer chain length and NP size.